2010
DOI: 10.1021/es101591a
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Ruminant PrPSc with Soils Is Influenced by Prion Source and Soil Type

Abstract: The persistence of prions within the environment is implicated in the horizontal transmission of ovine scrapie and cervid chronic wasting disease. Description of the interaction of prion strains derived from their natural hosts with a range of soil types is imperative in understanding how prions persist in the environment and, therefore, the characteristics of prion transmission. Here, we demonstrate that all detectable ovine scrapie and bovine BSE PrP(Sc) bind to a range of soil types within 24 h. This highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
(66 reference statements)
2
34
0
Order By: Relevance
“…Laboratory studies designed to examine prion adsorption to and persistence in soils typically rely on extraction of PrP TSE from soil particles followed by immunodetection (e.g., immunoblotting, enzyme-linked immunosorbent assay) as the primary means of measurement (Cooke et al, 2007;Huang et al, 2007;Jacobson et al, 2009Jacobson et al, , 2010Johnson et al, 2006;Leita et al, 2006;Ma et al, 2007;Maddison et al, 2010;Russo et al, 2009;Seidel et al, 2007). To date, effective elution of PrP TSE from soil particles has been accomplished only with anionic detergents such as sodium dodecyl sulfate (SDS) or sodium N-lauroylsarconsinate (sarkosyl) (Cooke et al, 2007;Johnson et al, 2006;Seidel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies designed to examine prion adsorption to and persistence in soils typically rely on extraction of PrP TSE from soil particles followed by immunodetection (e.g., immunoblotting, enzyme-linked immunosorbent assay) as the primary means of measurement (Cooke et al, 2007;Huang et al, 2007;Jacobson et al, 2009Jacobson et al, , 2010Johnson et al, 2006;Leita et al, 2006;Ma et al, 2007;Maddison et al, 2010;Russo et al, 2009;Seidel et al, 2007). To date, effective elution of PrP TSE from soil particles has been accomplished only with anionic detergents such as sodium dodecyl sulfate (SDS) or sodium N-lauroylsarconsinate (sarkosyl) (Cooke et al, 2007;Johnson et al, 2006;Seidel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The former ranks among the most widely used detection methods in experimental studies; the latter is typically considered the "gold standard" for prion detection. While recent studies have examined PrP TSE attachment to soils varying in organic carbon content (Cooke et al, 2007;Johnson et al, 2006;Maddison et al, 2010), the influence of natural organic matter (NOM) on PrP TSE measurement in soil or other environmental matrices has not been specifically investigated. Incomplete recovery and difficulty in separating proteins from co-extracted constituents of the soil matrix can complicate accurate quantification of proteins in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that prions bind rapidly, and largely irreversibly to soils, do not migrate through soil columns and can persist for years. 20,22,23 Furthermore, the interaction of prions with soil does not remove infectivity. 24,25 This interaction of prions with soil is influenced not only by the soil type but also by the prion source.…”
Section: Resultsmentioning
confidence: 99%
“…18 Within an experimental setting, infectivity and/or PrP TSE have been shown to bind rapidly, and mostly irreversibly, to a range of soils with distinct textures and mineral compositions. [18][19][20] The detailed understanding of how prions interact with soil is of key importance in understanding the risks involved in scrapie/CWD transmission in farmed and wild-life populations. The interaction of prions with soils is dictated by not only the soil type but also the prion strain/ host 20,21 indicating that studies detailing the interaction of prions with soil should ideally be performed using environmentally relevant prion sources; that is ovine scrapie, bovine BSE and/or cervid CWD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation